Effect of growth rate on microstructure evolution in directionally solidified Ti–47Al alloy. Issue 1 (January 2022) - Liu, Tong; Tao, Jing; Cai, Xiaoye; Chen, Dayong; Li, Jiansheng; Luo, Liangshun; Cheng, Zonghui; Su, Yanqing
Abstract: The microstructures and morphologies of directionally solidified Ti–47Al alloys with different growth rates ranging from 1 to 200 μm/s were investigated using the Bridgman directionally solidified method. The results showed that numerous columnar grains were formed along the growth direction with the onset of directional solidification. With a variation in the growth rate, the solid/liquid interface changed from a flat to cellular and to dendritic interface. The flat-to-cellular interface transition rate of the Ti–47Al alloy varied from 1 to 3 μm/s. When the growth rate was higher than 10 μm/s, the solid/liquid interface showed typical dendritic growth. During the directional solidification process, the main phase of the directionally solidified Ti–47Al alloy was the α phase, which can be attributed to the solute segregation, supercooling of the components, and contamination of the alloy melt by the Y2 O3 ceramic shell. After reaching the steady growth state during the directional solidification process, the solidification path of the alloy was: L→α→α+γ→(α2 +γ) + γ. With an increase in the growth rate, the primary dendrite spacing ( λ ) and lamellar spacing ( λs ) of the alloy decreased gradually. Abstract : Directional solidification; TiAl alloy; Solidification path; Lamellar structure.